(Un)ethical leadership, organizational identification and sensemaking: the BES case and its impact on employees - Fialho, Vanessa Marques (2017)
This paper provides an ongoing analysis to one of the biggest ethical and financial scandals in Portugal – Banco Espírito Santo (BES). BES was considered one of the three best banks but it went bankrupted and its employees were transferred to a new entity – Novo Banco. This study was conducted in order to provide an understanding of the employees’ side, which has been forgotten so far. An ethical scandal (sensebreaking) creates ambiguity and uncertainty which triggers new sensemaking processes in order to understand and derive meaning from the new reality. The methodology followed was semi-structured interviews to employees both from the branches and the central services. We found evidence that in organizations with strong identification, unethical behavior has a significant impact on followers’ – the new process of sensemaking is particularly important in this situation because employees suffer more from the disruption of their reality.